Survival Benefit of Hemodiafiltration Compared With Prolonged High-flux Hemodialysis (Iranian Journal of Kidney Diseases, 2016)
Introduction. Patients on dialysis have a high rate of death, mainly of cardiovascular cause. Nephrologists are actively looking for ways to improve patients' outcomes, and alternative dialysis strategies, such as long conventional hemodialysis and hemodiafiltration, are currently being investigated. The aim of this study was to compare anemia, nutrition, inflammation, mineral metabolism, and 3-year survival rates between patients treated with hemodiafiltration and prolonged high-flux hemodialysis (HFH). Materials and Methods. A total of 58 dialysis patients were divided into 2 groups to undergo hemodiafiltration 3 times weekly, 12 hours in total per week, or prolonged duration of HFH (≥ 15 h/w). One-year biochemical parameters were collected retrospectively, together with 36 months patients' survival (prospectively). Results. Patients in the HFH group had longer dialysis vintage; significantly higher levels of hemoglobin (despite less frequent use of erythropoietin-stimulating agents), serum albumin, serum calcium, and serum bicarbonate; and a lower intact parathyroid hormone level. Survival rates were comparable between the two groups. The Cox proportional hazard model showed that patients treated with longer HFH had a 32% relative risk reduction of mortality compared to patients treated with hemodiafiltration, but without statistical significance (hazard ratio, 0.68; 95% confidence interval, 0.21 to 2.20; adjusted for diabetes mellitus). Conclusions. Longer duration of hemodialysis with high-flux membranes had beneficial effects on anemia indexes, mineral metabolism, nutrition parameters, and acidosis in comparison with hemodiafiltration. However, hemodiafiltration did not offer a 36-months survival benefit over prolonged HFH.